1990
DOI: 10.1056/nejm199008093230601
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of the Cause of the Eosinophilia–Myalgia Syndrome Associated with Tryptophan Use

Abstract: The outbreak of the eosinophilia-myalgia syndrome in 1989 resulted from the ingestion of a chemical constituent that was associated with specific tryptophan-manufacturing conditions at one company. The chemical constituent represented by peak E may contribute to the pathogenesis of the eosinophilia-myalgia syndrome, or it may be a surrogate for another chemical that induces the syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
74
0
3

Year Published

1991
1991
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 341 publications
(78 citation statements)
references
References 15 publications
1
74
0
3
Order By: Relevance
“…This question arose when tryptophan became unavailable in various countries after tryptophan from a single manufacturer that contained a toxic trace impurity caused a number of deaths and disabilities due to a disorder that came to be called eosinophilia myalgia syndrome. 95 Krahn and colleagues 55 compared the effect of 100 g and 25 g tryptophandeficient amino acid mixtures. They confirmed the finding of my colleagues and I 89 that the 25 g mixture caused a much smaller decline in tryptophan availability and reported that the 8 participants who received both mixtures could not distinguish between them.…”
mentioning
confidence: 99%
“…This question arose when tryptophan became unavailable in various countries after tryptophan from a single manufacturer that contained a toxic trace impurity caused a number of deaths and disabilities due to a disorder that came to be called eosinophilia myalgia syndrome. 95 Krahn and colleagues 55 compared the effect of 100 g and 25 g tryptophandeficient amino acid mixtures. They confirmed the finding of my colleagues and I 89 that the 25 g mixture caused a much smaller decline in tryptophan availability and reported that the 8 participants who received both mixtures could not distinguish between them.…”
mentioning
confidence: 99%
“…Examples include drug-induced lupus (1), toxic oil syndrome (2,3), and contaminated L-tryptophan ingestion (4,5). Numerous mechanisms, based on in vitro evidence and animal models, have been proposed to explain how xenobiotics may induce or accelerate autoimmunity.…”
mentioning
confidence: 99%
“…The eosinophilia-myalgia syndrome was linked with tryptophan use after a case-control investigation, but a second case-control study was necessary to pin point the brand and retail lot numbers of the tryptophan responsible. 16 This was subsequently confirmed by chemical analysis of the implicated tryptophan brand. Rapid epidemiological investigation thus led to early containment measures and prevented further public exposure to the causative agent.…”
Section: Discussionmentioning
confidence: 64%